PERBUATAN MELAWAN HUKUM TERKAIT PEMBATALAN HASIL PEMENANG LELANG PENGADAAN PICTURE ARCHIVING COMMUNICATION SYSTEM (Analisis Putusan Nomor: 59/PDT G 2017/PN BNA) - Rahmansyah (2023)
In this study, the authors discuss the legal aspects of the cancellation of the auction results for the procurement of a picture archiving communication system in decision number. 59/pdt g 2017/pn bna which in the decision of unlawful acts, as well as to find out and analyze the settlement process and its results, in the case of canceling the auction results for the procurement of a picture archiving communication system which has legally gone through the procedure as stated in government regulation number 16 of 2018 amending presidential regulation number 54 of 2010 concerning procurement and also associated with administrative law 30 of 2014. but instead ended up in unlawful acts. The Study Findings Show that there are still inconsistencies in the handling of fact litigation cases (onrechtmatige overheidsdaad) which should have been carried out by administrative efforts up to the authority of the state administrative court, but are still being examined at the district court. The method used in this study is a normative juridical method which originates from legal sources by examining the laws and regulations related to this research. The conclusion obtained in this discussion is that with the existence of a district court decision that has determined the budget user (PA) and the budget user official (PPK) acts against the law and actually results in indications that can cause losses to state finances, because there is an obligation to pay material and immaterial losses as in the decision to act against.